Systematic Review: Perbandingan Lidah Buaya Dan Daun Kersen Dalam Menurunkan Kadar Gula Darah Penderita Diabetes Melitus - Nurmalasari; Sopiah, Popi; Astuti, Ayu (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Objective: Diabetes mellitus is a disease caused by the body's inability to produce insulin or decreased insulin production. This disease can reduce the quality of life and even death. Alternative medicine is an option for treating increased blood sugar levels in diabetes mellitus sufferers because it is considered cheap, easy and has few side effects. One of them is using aloe vera and cherry leaves. The aim of this research is to determine the comparison of aloe vera and cherry leaves in reducing blood sugar levels in diabetes sufferers through a literature study. Methods: The method used in this research is a systematic review by identifying and evaluating articles and journals via the Google Scholar, Pubmed and Semantic Scholar websites that were published from 2019 to 2024 using the keywords